If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(3*2g)=6(3*2g)
We move all terms to the left:
6(3*2g)-(6(3*2g))=0
We add all the numbers together, and all the variables
6(+3*2g)-(6(+3*2g))=0
We multiply parentheses
36g-(6(+3*2g))=0
We calculate terms in parentheses: -(6(+3*2g)), so:We add all the numbers together, and all the variables
6(+3*2g)
We multiply parentheses
36g
Back to the equation:
-(36g)
=0
g=0/1
g=0
| 2(3x+15)=2x+15+6x-37 | | 8(-b-4)=48 | | 85=x+89 | | 4(y-6)=-6 | | 17=19−2q | | 12=h2+8 | | -7.94+17.7f=20f+4.3-1.4f | | -6+7=3(2p-3)-(-10+4p) | | 12=h2+ 8 | | (3x+5)2=81 | | -0.9y=12.6+1.2y | | x=(34.5)•5 | | 5n^-3n-15=0 | | –2p=–p+3 | | y4+ 10=14 | | 16x^2+14x-6=0 | | -3(15j+18)+18j=3(-10j+8) | | 17=t3+ 15 | | 8.9x-12.7=22.9 | | 64=6c | | 2(x-31=5x+8 | | 7x-5x=180 | | 0=16x^2+18x+15 | | -0.53-9.4h=-0.23-8.4h | | (9m+10)*2=2 | | x-4.62=19.38 | | 2x-31=5x+8 | | 16+x=180 | | -13x-18=-4 | | 13a-5a(8)=0 | | 15c=60,c= | | √2x-5=√x-1 |